PELATIHAN PEMBUATAN LAPORAN KEUANGAN UMKM DI DESA KUBAH SENTANG KECAMATAN PANTAI LABU - Lusi Elviani Rangkuti; Farida Khairani Lubis; Shofwan Andri; Julienda Br. Harahap; Tika Indria (Jurnal Pengabdian Mitra Masyarakat, 2023)
Kubah Sentang is one of the villages in Pantai Labu sub-district, Deli Serdang Regency, North Sumatra province, Indonesia. It consists of two hamlets, namely Hamlet I and Hamlet II. Kubah Sentang Village is directly adjacent to Kuala Namu Deli Serdang International Airport, Pematang Monastery Village, Durian Village and Pantai Labu Pekan Village. The majority of the people in Dome Sentang Village are generally fishermen, farmers and livestock and plantation laborers. But in the sentang dome itself there are UMKM or home industries that produce food such as ombus ombus and raden galoh which still need coaching both in terms of marketing and financial reports. The purpose of this community service is for training in making MSME financial reports at the Sentang Dome. The result of this service is that the people of Sentang Dome understand how to make simple financial reports and understand how to record income and expenses so that the cash books owned by MSMEs in Sentang Dome can be recorded neatly and easy to understand. Starting from recording transactions in the cash book to making journals and up to making simple financial reports consisting of profit and loss reports, reports on changes in capital and statements of financial position